783 Brachial Plexopathy Secondary to Prone Position Used in The Treatment of a Ventilated Patient With COVID-19: A Case Report and Service Improvement Recommendations. (4th May 2021) - Baldwin, A; Truelove, A; Ali, T
Abstract: Introduction: Prone position has been recommended by many authorities as part of the management of ventilated patients with COVID-19. However, proning with concurrent use of sedation and muscle relaxants carries the hypothetical risk of brachial plexus injuries, thought to be due to stretch and compression of the abducted shoulder. Case: : : We report the case of a long-stay critical care patient who required frequent proning due to SARS-CoV-2 infection, and who presented with new right upper limb weakness. This case was referred to our local plastic surgery service and an injury to the upper trunk of the right brachial plexus was confirmed on nerve conduction studies. Recommendations: : Following this case, we made adaptations to our local practice and modified our prone-specific SSKIN bundle (originally created to prevent pressure sores) to include a section on 'Nerves', with an accompanying diagram. We dubbed this the SSKINN bundle. This ensured safe prone positioning. We encourage other hospitals to put in place similar interventions. Conclusions: We present this as a pathology to consider in patients proned during the COVID-19 pandemic; and recommend checking for signs of focal neurological deficits of the upper limb upon removal of paralysis and sedation, with early referral of suspected cases.